Membrane electrode and preparation method thereof, fuel cell and electrolytic cell
By forming a porous breathable layer on both sides of the proton exchange membrane of the membrane electrode and pressing the catalytic layer at its opposite point, the problem of membrane particles blocking the catalytic layer is solved, and the breathability of the membrane electrode and the water electrolytic performance of the fuel cell are improved.
Patent Information
- Application Number
- CN202411675335.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
During the preparation of membrane electrodes, the swelling shape of the proton exchange membrane causes membrane particles to squeeze into the pores of the electrode catalytic layer, causing hole blockage, affecting the transmission and discharge of oxygen, and thus reducing the performance of water electrolysis.
A porous breathable layer is formed on the opposite sides of the proton exchange membrane, and the anode layer and a cathode layer are pressed on the side where the porous breathable layer is away from the proton exchange membrane to form a film electrode. The porous breathable layer ink is transferred onto the proton exchange membrane by thermal transfer method, forming anode porous breathable layer and cathode porous breathable layer to prevent membrane particles from entering the catalytic layer.
By setting up a porous breathable layer, membrane particles are prevented from clogging the pores of the catalytic layer, and the breathability of the anode catalytic layer and the catalytic layer is improved, thereby improving the water electrolytic performance of the fuel cell.
Smart Images

Figure CN119518042A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of terminal technology, and in particular to a membrane electrode and a preparation method thereof, a fuel cell and an electrolyzer. Background Art
[0002] At present, in the preparation process of membrane electrode, the electrode catalyst layer is usually directly formed on the surface of the proton exchange membrane, resulting in direct contact between the proton exchange membrane and the electrode catalyst layer. However, due to the particularity of the material of the proton exchange membrane itself, it has a swelling shape, which will squeeze the membrane particles into the pores of the electrode catalyst layer, causing pore blockage, affecting the transmission and discharge of oxygen, and causing the performance of water electrolysis to decline. Summary of the invention
[0003] The present application provides a membrane electrode and a preparation method thereof, a fuel cell and an electrolyzer to solve the deficiencies in the related art.
[0004] According to a first aspect of an embodiment of the present application, a method for preparing a membrane electrode is provided, comprising:
[0005] obtaining a proton exchange membrane, an anode layer, and a cathode layer;
[0006] forming porous gas-permeable layers on opposite sides of the proton exchange membrane;
[0007] The anode layer is pressed onto the side of the porous gas-permeable layer facing away from the proton exchange membrane;
[0008] The cathode layer is pressed onto the side of the porous gas-permeable layer on the other side facing away from the proton exchange membrane to obtain the membrane electrode.
[0009] Optionally, forming porous gas-permeable layers on opposite sides of the proton exchange membrane comprises:
[0010] Configure porous air-permeable layer ink;
[0011] Applying the porous air-permeable layer ink to a substrate;
[0012] The porous air-permeable layer ink coated on the substrate is transferred to the proton exchange membrane by a thermal transfer method to form the porous air-permeable layer.
[0013] Optionally, the configuration of the porous air-permeable layer ink includes:
[0014] The Ti-based nanoparticles and deionized water are mixed and dispersed by ultrasonic stirring in a water bath to obtain a first dispersion;
[0015] Adding Dupont Nafion D520 solution and solvent to the first dispersion in sequence to obtain a first mixed solution, wherein the solvent includes ethanol, n-propanol or isopropanol;
[0016] The first mixed liquid is sequentially dispersed and degassed to obtain a porous air-permeable layer ink.
[0017] Optionally, the mass ratio of Ti-based nanoparticles, Dupont Nafion D520 solution, deionized water, and solvent is 1:5:1:0.2;
[0018] Alternatively, the step of sequentially adding the Dupont Nafion D520 solution and the solvent to the first dispersion to obtain a mixed solution comprises: after adding the Dupont Nafion D520 solution and the solvent, planetary ball milling at 1500 r / min for more than 30 min to obtain the first mixed solution;
[0019] Alternatively, the sequentially dispersing and degassing treatment of the mixed liquid includes: using an ultrasonic stirring rod to disperse the mixed liquid at a set dispersion frequency for a set time, and then placing the dispersed first mixed liquid in a centrifugal degassing machine for degassing to obtain a porous air-permeable layer of ink.
[0020] Optionally, obtaining the anode layer / cathode layer includes:
[0021] Obtain a titanium mesh skeleton;
[0022] One of the iridium oxide particles and the carbon-supported platinum catalyst is mixed with deionized water, and dispersed by ultrasonic stirring in a water bath to obtain a second dispersion, wherein the iridium oxide particles are used to form an anode catalyst layer ink, and the carbon-supported platinum catalyst is used to form a cathode catalyst layer ink.
[0023] Adding Dupont Nafion D520 solution and solvent to the second dispersion in sequence to obtain a second mixed solution, wherein the solvent includes ethanol, n-propanol or isopropanol;
[0024] After dispersing and degassing the second mixed solution in sequence, an anode catalyst layer ink or a cathode catalyst layer ink is obtained;
[0025] The anode catalyst layer ink is sprayed on the titanium mesh skeleton, and a polymer layer is sprayed on the surface of the anode catalyst layer ink to obtain the anode layer, or the cathode catalyst layer ink is sprayed on the titanium mesh skeleton, and a polymer layer is sprayed on the surface of the cathode catalyst layer ink to obtain the cathode layer.
[0026] Optionally, the mass ratio of the iridium oxide particles, the Dupont Nafion D520 solution, the deionized water and the solvent is 1:2.5:0.8:50.
[0027] Optionally, the mass ratio of the carbon-supported platinum catalyst, the Dupont Nafion D520 solution, the deionized water and the solvent is 1:7:7:50;
[0028] Alternatively, the step of sequentially adding the Dupont Nafion D520 solution and n-propanol to the dispersion to obtain a mixed solution comprises: after adding the Dupont Nafion D520 solution and n-propanol, planetary ball milling at 1500 r / min for more than 30 min to obtain the mixed solution;
[0029] Alternatively, the sequentially dispersing and degassing the mixed liquid comprises: using an ultrasonic stirring rod to disperse the mixed liquid at a set dispersion frequency for a set time, and then placing the dispersed mixed liquid in a centrifugal degassing machine for degassing.
[0030] According to a second aspect of an embodiment of the present disclosure, there is provided a membrane electrode, comprising:
[0031] Proton exchange membrane;
[0032] Anode layer;
[0033] an anode porous gas-permeable layer, wherein the anode porous gas-permeable layer is attached between the first side of the proton exchange membrane and the anode layer;
[0034] cathode layer;
[0035] The cathode porous gas-permeable layer is attached between the second side of the proton exchange membrane and the cathode layer, and the first side and the second side are arranged opposite to each other.
[0036] According to a third aspect of the embodiments of the present disclosure, a fuel cell is provided, comprising a mold electrode obtained by the preparation method as described in any one of the above embodiments, or comprising a membrane electrode as described in any one of the above embodiments.
[0037] According to a third aspect of the embodiments of the present disclosure, there is provided an electrolytic cell comprising a mold electrode obtained by the preparation method as described in any one of the above embodiments, or comprising a membrane electrode as described in any one of the above embodiments.
[0038] The technical solution provided by the embodiments of the present application may have the following beneficial effects:
[0039] It can be seen from the above embodiments that in the membrane electrode prepared by the present application, an anode porous air-permeable layer is arranged between the proton exchange membrane and the anode layer, and a cathode porous air-permeable layer is arranged between the proton exchange membrane and the cathode layer. Therefore, the membrane particles squeezed into the membrane due to the swelling shape of the proton exchange membrane will enter the anode porous air-permeable layer and the cathode porous air-permeable layer, and will not cause clogging of the anode catalyst layer contained in the anode layer and the cathode catalyst layer contained in the cathode layer, which is beneficial to improving the permeability of the anode catalyst layer and the cathode catalyst layer.
[0040] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0042] Figure 1 The present invention is a flow chart of a method for preparing a membrane electrode according to an exemplary embodiment.
[0043] Figure 2 is a schematic cross-sectional view of a membrane electrode according to an exemplary embodiment.
[0044] Figure 3 The figure is a flow chart of a method for preparing a porous gas-permeable layer according to an exemplary embodiment.
[0045] Figure 4 is a flow chart of a method for preparing an anode layer according to an exemplary embodiment.
[0046] Figure 5 is a flow chart of a method for preparing a cathode layer according to an exemplary embodiment. DETAILED DESCRIPTION
[0047] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application. Instead, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the appended claims.
[0048] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0049] It should be understood that although the terms first, second, third, etc. may be used in the present application to describe various information, these information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Depending on the context, the word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining".
[0050] Figure 1 is a flow chart of a method for preparing a membrane electrode according to an exemplary embodiment. Figure 1 As shown, the preparation flow chart of the membrane electrode may include the following steps:
[0051] In step 101, a proton exchange membrane, an anode layer, and a cathode layer are obtained.
[0052] In this embodiment, the proton exchange membrane can be selected according to the needs, for example, the FUMA-FS-990-PK model proton exchange membrane can be used, and the selected proton exchange membrane needs to be pretreated to facilitate the subsequent process between the surface of the proton exchange membrane and other layer structures. For example, the FUMA-FS-990-PK model proton exchange membrane can be hot-pressed, and the hot-pressing temperature, hot-pressing pressure, and hot-pressing time can all be selected as needed. For example, the hot-pressing temperature can be 110°C, the hot-pressing pressure can be 10MPa, and the hot-pressing time can be 3 minutes.
[0053] The anode layer can be formed by spraying an anode catalyst layer on a porous transmission substrate, and the anode catalyst layer contains precious metal materials, which can enhance or accelerate the oxidation reaction of hydrogen. Similarly, the cathode layer can be formed by spraying a cathode catalyst layer on a porous transmission substrate, and the cathode catalyst layer contains precious metal materials, which can enhance or accelerate the oxidation reaction of hydrogen and improve the reaction efficiency.
[0054] In step 102, porous gas-permeable layers are formed on opposite sides of the proton exchange membrane.
[0055] In this embodiment, a porous gas-permeable layer ink may be pre-prepared, and then a suitable process may be used to form a porous gas-permeable layer on both sides of the proton exchange membrane. Figure 2 As shown in the figure, a schematic cross-sectional view of a membrane electrode is provided, the membrane electrode comprises a proton exchange membrane 1, an anode porous gas-permeable layer 2 and a cathode porous gas-permeable layer 3, wherein the anode porous gas-permeable layer 2 is formed on the upper surface of the proton exchange membrane 1, and the cathode porous gas-permeable layer 3 is formed on the lower surface of the proton exchange membrane 1. Among them, the porous gas-permeable layer ink does not contain precious metal materials, and does not participate in or accelerate or improve the efficiency of the oxidation reaction of hydrogen, and its function is to transport hydrogen ions.
[0056] In step 103, the anode layer is pressed onto the side of the porous gas-permeable layer facing away from the proton exchange membrane.
[0057] In step 104, the cathode layer is pressed onto the side of the other porous gas-permeable layer facing away from the proton exchange membrane to obtain the membrane electrode.
[0058] In this embodiment, Figure 2 As shown, the membrane electrode may also include an anode layer 4 and a cathode layer 5. In step 104, the anode layer 4 may be pressed on the side of the anode porous gas-permeable layer away from the proton exchange membrane 1, and the cathode layer 5 may be pressed on the side of the cathode porous gas-permeable layer away from the proton exchange membrane 1, thereby obtaining a membrane electrode. Among them, the hot pressing temperature, hot pressing pressure and hot pressing time can all be selected as needed. For example, the hot pressing temperature may be 130°C, the hot pressing pressure may be 5MPa, and the hot pressing time may be 5 minutes. The hot pressing conditions for pressing the anode layer 4 and pressing the cathode layer 5 may be the same or different.
[0059] It can be seen from the above embodiments that in the membrane electrode prepared by the present application, an anode porous gas-permeable layer is arranged between the proton exchange membrane 1 and the anode layer 4, and a cathode porous gas-permeable layer 3 is arranged between the proton exchange membrane 1 and the cathode layer 5. Therefore, the membrane particles squeezed into the membrane due to the swelling shape of the proton exchange membrane 1 will enter the anode porous gas-permeable layer 2 and the cathode porous gas-permeable layer 3, and will not cause clogging of the anode catalyst layer contained in the anode layer 4 and the cathode catalyst layer contained in the cathode layer 5, which is beneficial to improving the permeability of the anode catalyst layer and the cathode catalyst layer.
[0060] like Figure 3 As shown, Figure 3 A method for preparing a porous gas-permeable layer formed on the surface of a proton exchange membrane 1 is provided, which may specifically include the following steps:
[0061] In step 301, a porous air-permeable layer ink is prepared.
[0062] In this embodiment, Ti-based nanoparticles and deionized water can be mixed and dispersed by water bath ultrasonic stirring to obtain a first dispersion; Dupont Nafion D520 solution and solvent are added to the first dispersion in sequence to obtain a first mixed solution, and the first mixed solution is dispersed and degassed in sequence to obtain a porous air-permeable layer ink.
[0063] Wherein, the solvent may include ethanol, n-propanol or isopropanol, the Ti-based nanoparticles may include TiO2, TiN, TiC and other particles, and the form may be nanospheres, nanorods or nanotubes, and the particle size range of the Ti-based nanoparticles may be between 50nm and 250nm. For example, TiO2 nanorods with a diameter of 50nm and a length of 200nm and deionized water may be mixed at room temperature of 25°C, and the mixed solution may be stirred by ultrasonic stirring in a water bath so that the TiO2 nanorods are evenly dispersed in the deionized water to obtain a first dispersion. The duration of ultrasonic stirring in a water bath may be selected as required, for example, stirring may be performed for 3 minutes or 5 minutes or other durations.
[0064] Add Dupont Nafion D520 solution and solvent to the first dispersion in sequence. Taking n-propanol as the solvent, for example, Dupont Nafion D520 solution can be added to the first dispersion first, then n-propanol can be added, and then the first dispersion can be subjected to planetary ball milling at 1500r / min for more than 30min to obtain a first mixed solution. In order to make the first mixed solution uniformly dispersed, the first mixed solution after ball milling can be subjected to dispersion treatment, such as using an ultrasonic stirring rod to disperse the first mixed solution at a set dispersion frequency for a set time. For example, a 40kHz ultrasonic stirring rod can be used to disperse the first mixed solution for 10min, and the dispersion frequency can be 5 seconds for dispersion and 3 seconds for rest, or other dispersion frequencies can be used, and the present application does not limit this.
[0065] For the first mixed liquid stirred by the ultrasonic stirring rod, the dispersed first mixed liquid can be placed in a centrifugal defoamer for degassing, for example, the degassing time can be 20 seconds, and then a porous air-permeable layer ink can be obtained.
[0066] In the porous air-permeable layer ink, the mass ratio of Ti-based nanoparticles, Dupont Nafion D520 solution, deionized water and solvent is 1:5:1:0.2; the mass ratio of the polymer material in the Dupont Nafion solution to the Ti-based nanoparticles is 0.15-0.8; the mass ratio of deionized water to the solvent is 5-20, and the mass ratio of the solid content of the porous air-permeable layer ink is 15%-30%.
[0067] In step 302, the porous air-permeable layer ink is applied to a substrate.
[0068] In step 303, the porous air-permeable layer ink coated on the substrate is transferred to the proton exchange membrane by a thermal transfer method to form the porous air-permeable layer.
[0069] In this embodiment, after the porous air-permeable layer ink is applied to the substrate, it can be dried under set environmental conditions to keep the porous air-permeable layer ink dry, and then the porous air-permeable layer ink is transferred to the upper and lower surfaces of the proton exchange membrane by thermal transfer, thereby obtaining the anode porous air-permeable layer 2 and the cathode porous air-permeable layer 3. Among them, the process conditions of the thermal transfer method can be selected as needed, for example, the temperature range of the thermal transfer method can be 130°C-180°C, and the pressure is 2MPa-10MPa. Moreover, the method of transferring the porous air-permeable layer ink by thermal transfer to form a porous air-permeable layer can be implemented under dry conditions. Compared with the method of spraying the porous air-permeable layer ink to form a porous air-permeable layer, it can avoid the proton exchange membrane 1 from being wet and wrinkled, which is beneficial to protecting the proton exchange membrane 1.
[0070] like Figure 4 As shown, Figure 4 A method for preparing an anode layer 4 is provided, which may specifically include the following steps:
[0071] In step 401, an anode titanium mesh skeleton is obtained.
[0072] In this embodiment, the anode titanium mesh skeleton may be pretreated. For example, a 200 μm thick, 200-mesh TA1 titanium mesh may be selected as the anode titanium mesh skeleton, and the TA1 titanium mesh may be electroplated with platinum metal with a plating thickness of 500 nm.
[0073] In step 402, iridium oxide particles are mixed with deionized water, and dispersed by ultrasonic stirring in a water bath to obtain a second dispersion.
[0074] In this embodiment, the particle size of the iridium oxide particles can be selected as needed. For example, iridium oxide particles with a particle size of 2-20 nm can be selected and mixed with deionized water at room temperature of 25°C, and the mixed solution can be stirred by ultrasonic stirring in a water bath so that the iridium oxide particles are evenly dispersed in the deionized water to obtain a second dispersion. The stirring time of ultrasonic stirring in a water bath can be selected as needed, for example, stirring can be 3 minutes or 5 minutes or other time.
[0075] In step 403, Dupont Nafion D520 solution and solvent are added to the second dispersion in sequence to obtain a second mixed solution.
[0076] In this embodiment, the solvent may include ethanol, n-propanol or isopropanol. Taking n-propanol as an example, Dupont Nafion D520 solution may be added to the second dispersion first, then n-propanol may be added, and then the mixture may be planetarily ball milled at 1500 r / min for more than 30 min to obtain a second mixed solution.
[0077] In step 404, the second mixed solution is dispersed and degassed in sequence to obtain an anode catalyst layer ink.
[0078] In this embodiment, in order to make the second mixed liquid evenly dispersed, the second mixed liquid after ball milling can be dispersed, such as using an ultrasonic stirring rod to disperse the second mixed liquid at a set dispersion frequency for a set time. For example, a 40kHz ultrasonic stirring rod can be used to disperse the second mixed liquid for 10 minutes, and the dispersion frequency can be 5 seconds of dispersion and 3 seconds of pause, or other dispersion frequencies can be used, and the present application does not limit this.
[0079] For the second mixed liquid stirred by the ultrasonic stirring rod, the dispersed second mixed liquid can be placed in a centrifugal defoamer for degassing, for example, the degassing time can be 20 seconds, and then the anode catalyst layer ink is obtained. In the anode catalyst layer ink, the mass ratio of iridium oxide particles, Dupont Nafion D520 solution, deionized water and solvent is 1:2.5:0.8:50.
[0080] In step 405 , the anode catalyst layer ink is sprayed onto the anode titanium mesh skeleton, and a polymer layer is sprayed on the surface of the anode catalyst layer ink to obtain the anode layer 4 .
[0081] In this embodiment, the iridium oxide loading in the anode layer 4 is 0.7 mg / cm2, and the polymer layer can be formed by spraying Dupont Nafion D520 solution on the surface of the anode catalyst layer, and the polymer loading is 0.1 mg / cm2.
[0082] like Figure 5 As shown, Figure 5 A method for preparing a cathode layer 5 is provided, which may specifically include the following steps:
[0083] In step 501, a cathode titanium mesh skeleton is obtained.
[0084] In this embodiment, the cathode titanium mesh skeleton may be pretreated. For example, a 200 μm thick, 200-mesh TA1 titanium mesh may be selected as the cathode titanium mesh skeleton, and the TA1 titanium mesh may be electroplated with platinum metal with a thickness of 500 nm.
[0085] In step 502, the carbon-supported platinum catalyst is mixed with deionized water, and dispersed by water bath ultrasonic stirring to obtain a second dispersion.
[0086] In this embodiment, the particle size of the iridium oxide particles can be selected as needed. For example, iridium oxide particles with a particle size of 2-20 nm can be selected and mixed with deionized water at room temperature of 25°C, and the mixed solution can be stirred by ultrasonic stirring in a water bath so that the iridium oxide particles are evenly dispersed in the deionized water to obtain a second dispersion. The stirring time of ultrasonic stirring in a water bath can be selected as needed, for example, stirring can be 3 minutes or 5 minutes or other time.
[0087] In step 503, Dupont Nafion D520 solution and solvent are added to the second dispersion liquid in sequence to obtain a second mixed liquid.
[0088] In this embodiment, the solvent may include ethanol, n-propanol or isopropanol. Taking n-propanol as an example, Dupont Nafion D520 solution may be added to the second dispersion first, then n-propanol may be added, and then the mixture may be planetarily ball milled at 1500 r / min for more than 30 min to obtain a second mixed solution.
[0089] In step 504, the second mixed solution is dispersed and degassed in sequence to obtain cathode catalyst layer ink.
[0090] In this embodiment, in order to make the second mixed liquid evenly dispersed, the second mixed liquid after ball milling can be dispersed, such as using an ultrasonic stirring rod to disperse the second mixed liquid at a set dispersion frequency for a set time. For example, a 50kHz ultrasonic stirring rod can be used to disperse the second mixed liquid for 10 minutes. The dispersion frequency can be 5 seconds of dispersion and 3 seconds of pause, or other dispersion frequencies can be used. The present application does not limit this.
[0091] For the second mixed liquid stirred by the ultrasonic stirring rod, the dispersed second mixed liquid can be placed in a centrifugal defoamer for degassing, for example, the degassing time can be 20 seconds, and then the cathode catalyst layer ink is obtained. In the cathode catalyst layer ink, the mass ratio of carbon-supported platinum catalyst, Dupont Nafion D520 solution, deionized water and solvent is 1:7:7:50.
[0092] In step 505 , the cathode catalyst layer ink is sprayed onto the cathode titanium mesh skeleton, and a polymer layer is sprayed on the surface of the cathode catalyst layer ink to obtain the cathode layer 5 .
[0093] In this embodiment, the platinum loading in the cathode layer 5 is 0.25 mg / cm2, and the polymer layer can be formed by spraying DupontNafion D520 solution on the surface of the cathode catalyst layer, and the polymer loading is 0.1 mg / cm2.
[0094] Based on the technical solution of the present disclosure, a fuel cell is also provided. The fuel cell may include the membrane electrode described in any of the aforementioned embodiments, or include a membrane electrode obtained by the preparation method described in any of the aforementioned embodiments.
[0095] Based on the technical solution of the present disclosure, an electrolytic cell is also provided. The electrolytic cell may include the membrane electrode described in any of the aforementioned embodiments, or include a membrane electrode obtained by the preparation method described in any of the aforementioned embodiments.
[0096] The electrolyzer and fuel cell described in the foregoing embodiments may be applied to the same hydrogen energy storage system, or in the same hydrogen energy storage system, only the membrane electrode of the fuel cell or the membrane electrode of the electrolyzer may adopt the membrane electrode solution provided in this application, and this application does not impose any restrictions on this.
[0097] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the disclosure disclosed herein. The present application is intended to cover any modification, use or adaptation of the present application, which follows the general principles of the present application and includes common knowledge or customary techniques in the art that are not disclosed in the present application. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present application are indicated by the following claims.
[0098] It should be understood that the present application is not limited to the precise structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
Claims
1. A method for preparing a membrane electrode, characterized in that: include: obtaining a proton exchange membrane, an anode layer, and a cathode layer; forming porous gas-permeable layers on opposite sides of the proton exchange membrane; The anode layer is pressed onto the side of the porous gas-permeable layer facing away from the proton exchange membrane; The cathode layer is pressed onto the side of the porous gas-permeable layer on the other side facing away from the proton exchange membrane to obtain the membrane electrode.
2. The method for preparing a membrane electrode according to claim 1, characterized in that: The forming of porous gas-permeable layers on opposite sides of the proton exchange membrane comprises: Configure porous air-permeable layer ink; Applying the porous air-permeable layer ink to a substrate; The porous air-permeable layer ink coated on the substrate is transferred to the proton exchange membrane by a thermal transfer method to form the porous air-permeable layer.
3. The method for preparing a membrane electrode according to claim 2, characterized in that: The porous air-permeable layer ink is configured as follows: The Ti-based nanoparticles and deionized water are mixed and dispersed by ultrasonic stirring in a water bath to obtain a first dispersion; Adding Dupont Nafion D520 solution and solvent to the first dispersion in sequence to obtain a first mixed solution, wherein the solvent includes ethanol, n-propanol or isopropanol; The first mixed liquid is sequentially dispersed and degassed to obtain a porous air-permeable layer ink.
4. The method for preparing a membrane electrode according to claim 3, characterized in that: The mass ratio of Ti-based nanoparticles, Dupont Nafion D520 solution, deionized water, and solvent was 1:5:1:0.2; Alternatively, the step of sequentially adding the Dupont Nafion D520 solution and the solvent to the first dispersion to obtain a mixed solution comprises: after adding the Dupont Nafion D520 solution and the solvent, planetary ball milling at 1500 r / min for more than 30 min to obtain the first mixed solution; Alternatively, the sequentially dispersing and degassing treatment of the mixed liquid includes: using an ultrasonic stirring rod to disperse the mixed liquid at a set dispersion frequency for a set time, and then placing the dispersed first mixed liquid in a centrifugal degassing machine for degassing to obtain a porous air-permeable layer of ink.
5. The method for preparing a membrane electrode according to claim 1, characterized in that: Obtaining the anode layer / cathode layer includes: Obtain a titanium mesh skeleton; One of the iridium oxide particles and the carbon-supported platinum catalyst is mixed with deionized water, and dispersed by ultrasonic stirring in a water bath to obtain a second dispersion, wherein the iridium oxide particles are used to form an anode catalyst layer ink, and the carbon-supported platinum catalyst is used to form a cathode catalyst layer ink. Adding Dupont Nafion D520 solution and solvent to the second dispersion in sequence to obtain a second mixed solution, wherein the solvent includes ethanol, n-propanol or isopropanol; After dispersing and degassing the second mixed solution in sequence, an anode catalyst layer ink or a cathode catalyst layer ink is obtained; The anode catalyst layer ink is sprayed on the titanium mesh skeleton, and a polymer layer is sprayed on the surface of the anode catalyst layer ink to obtain the anode layer; or the cathode catalyst layer ink is sprayed on the titanium mesh skeleton, and a polymer layer is sprayed on the surface of the cathode catalyst layer ink to obtain the cathode layer.
6. The method for preparing a membrane electrode according to claim 5, characterized in that: The mass ratio of the iridium oxide particles, the Dupont Nafion D520 solution, the deionized water and the solvent is 1:2.5:0.8:
50.
7. The method for preparing a membrane electrode according to claim 5, characterized in that: The mass ratio of the carbon-supported platinum catalyst, the Dupont Nafion D520 solution, the deionized water and the solvent is 1:7:7:50; Alternatively, the step of sequentially adding the Dupont Nafion D520 solution and n-propanol to the dispersion to obtain a mixed solution comprises: after adding the Dupont Nafion D520 solution and n-propanol, planetary ball milling at 1500 r / min for more than 30 min to obtain the mixed solution; Alternatively, the sequentially dispersing and degassing the mixed liquid comprises: using an ultrasonic stirring rod to disperse the mixed liquid at a set dispersion frequency for a set time, and then placing the dispersed mixed liquid in a centrifugal degassing machine for degassing.
8. A membrane electrode, characterized in that: include: Proton exchange membrane; Anode layer; an anode porous gas-permeable layer, wherein the anode porous gas-permeable layer is attached between the first side of the proton exchange membrane and the anode layer; cathode layer; The cathode porous gas-permeable layer is attached between the second side of the proton exchange membrane and the cathode layer, and the first side and the second side are arranged opposite to each other.
9. A fuel cell, characterized in that: It includes a mold electrode obtained by the preparation method as described in any one of 1-7, or includes a membrane electrode as described in claim 8.
10. An electrolytic cell, characterized in that: It includes a mold electrode obtained by the preparation method as described in any one of 1-7, or includes a membrane electrode as described in claim 8.
Citation Information
Patent Citations
Membrane electrode for proton exchange membrane water electrolysis battery and preparation thereof
CN101388463A
Membrane electrode of long-life fuel cell with porous adsorption layer and preparation method thereof
CN101853943A
Fuel cell membrane electrode assembly formed by growing whiskers and preparation method
CN112259747A
Composite proton exchange membrane, preparation method thereof and fuel cell
CN114843568A
Membrane electrode for proton exchange membrane fuel cell and preparation method thereof
CN115939417A